2020
DOI: 10.2147/idr.s259562
|View full text |Cite
|
Sign up to set email alerts
|

<p>Carbapenemase Producing Gram-Negative Bacteria in Tunisia: History of Thirteen Years of Challenge</p>

Abstract: The wide spread of multidrug-resistant bacteria, particularly carbapenem-resistant Gram-negative bacteria (CR-GNB), constitutes a major public health threat worldwide, owing to the limited therapeutic options. This review will describe and uncover the Tunisian experience in the challenge against carbapenem resistance. Indeed, we illuminate on the dissemination of CR-GNB in different hospitals, animals, and other natural environments in this country. We resumed the different carbapenemase variants detected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 75 publications
(86 reference statements)
0
17
1
Order By: Relevance
“…Actually, most of the acquired resistance genes are mobilized by these plasmids that favor the spread of these resistance genes between various species. 16 Discussion C. freundii was seldom studied not only in Tunisia but also all over the world and has usually been considered as an environmental contaminant. 1 Nevertheless, with the general increase of antimicrobial resistance, it has been reported that multiresistant C. freundii has been responsible for severe infections in neonates and in immunocompromised patients with therapeutic impasses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Actually, most of the acquired resistance genes are mobilized by these plasmids that favor the spread of these resistance genes between various species. 16 Discussion C. freundii was seldom studied not only in Tunisia but also all over the world and has usually been considered as an environmental contaminant. 1 Nevertheless, with the general increase of antimicrobial resistance, it has been reported that multiresistant C. freundii has been responsible for severe infections in neonates and in immunocompromised patients with therapeutic impasses.…”
Section: Resultsmentioning
confidence: 99%
“…In Tunisia, it has been reported that the most common species acquiring carbapenemase encoding genes were Acinetobacter baumannii, Klebsiella pneumoniae, and Pseudomonas aeruginosa. 16 Only one carbapenemase producing C. freundii strain has been hitherto detected in Tunisia. 16,17 Many carbapenemases are encoded on plasmids, which facilitate the spread of resistance genes among microorganisms of the same species or even among different bacterial species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining genes were not detected despite several repetition of PCR amplification of the corresponding genes. VIM variants, especially VIM-1, are largely found in clinical Gramnegative bacteria in Italy and Greece and are the main metallo-carbapenemase detected in Tunisia among clinical Pseudomonas aeruginosa and K. pneumoniae; however, they are scarily reported in E. coli and Enterobacter complex (Dziri et al 2020). The IMI carbapenemases, belonging to Ambler class A carbapenemases and typically associated with the Enterobacter cloacae complex, have never been reported in Tunisia (Madec et al 2017;Dziri et al 2020;Bonnin et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…1,2 Indeed, it is considered one of the last-resort antibiotics used for the treatment of severe infections, caused in particular by carbapenem-resistant Gram-negative bacteria. 3,4 Several studies have revised and evaluated the colistin dosing regimen, as well as the best way to use and minimize its toxicity, sos as to ensure its safety and efficacy. [5][6][7][8] Colistin consumption has been continuously increasing since 2000 worldwide, including low-income countries.…”
Section: Introductionmentioning
confidence: 99%